Máscaras e respiradores: uma revisão sobre suas características e seus impactos ambientais, e a influência da pandemia de COVID-19 - Rocha, Thais Helena dos Santos (Universidade Federal de São Carlos, 2021)
The COVID-19 pandemic brought an unprecedented use of masks and respirators for the healthcare workers and population. World Health Organization estimated the monthly needs of 129 billion masks. In order to prevent the spread of the disease, the widespread use of masks and respirators and their mismanagement may result in greater environmental contamination. The main objective of this work is to review the concepts of masks, respirators and polymeric materials, and to verify their environmental impacts, in addition to the possible strategies to minimize impacts. The masks and respirators are made of non-woven material, synthetic fibers (plastics), which filter particles, such as viruses, by the mechanisms of diffusion, direct interception, inertial deposition, sedimentation by gravitational force, and electrostatic deposition. These plastics objects can have negative consequences for the environment, such as animal entanglement, ingestion by animals, the release of microplastics and additives dangerous to health and the environment, persistence, among others. To reduce harmful impacts strategies should be adopted for pollution mitigation, such as improvements in waste management, recycling, reuse, use of sustainable plastics, public awareness of the use and disposal of plastics, and environmental remediation techniques: technologies for collecting plastics in aquatic environments and biotechnologies for the degradation of plastics.
Masks and respirators: a review of their environmental characteristics and impacts, and the influence of the COVID-19 pandemic
Keywords: Máscaras; COVID-19; Plásticos; Poluição; Impactos Ambientais; Masks; Plastics; Pollution; Environmental impacts; CIENCIAS EXATAS E DA TERRA::QUIMICA